.
a² - b² = (a + b) · (a - b) - формула разности квадратов
(25,7 + 14,3) · (25,7 - 14,3) : 20 = 40 · 11,4 : 20 = 11,4 · (40 : 20) = 11,4 · 2 = 22,8.
1) 25,7² = 25,7 · 25,7 = 660,49
2) 14,3² = 14,3 · 14,3 = 204,49
3) 660,49 - 204,49 = 456
4) 456 : 20 = 22,8
ответ: Б) 22,8.
.
a² - b² = (a + b) · (a - b) - формула разности квадратов
(25,7 + 14,3) · (25,7 - 14,3) : 20 = 40 · 11,4 : 20 = 11,4 · (40 : 20) = 11,4 · 2 = 22,8.
.
1) 25,7² = 25,7 · 25,7 = 660,49
2) 14,3² = 14,3 · 14,3 = 204,49
3) 660,49 - 204,49 = 456
4) 456 : 20 = 22,8
ответ: Б) 22,8.